Phylogenetic confirmation of the genus Robbea (Nematoda: Desmodoridae, Stilbonematinae) with the description of three new species - Ott, J. A.; Gruber-Vodicka, H. R.; Leisch, N.; Zimmermann, J. (Systematics and Biodiversity, 2014)
The Stilbonematinae are a monophyletic group of marine nematodes that are characterized by a coat of thiotrophic bacterial symbionts. Among the ten known genera of the Stilbonematinae, the genus Robbea G ERLACH 1956 had a problematic taxonomic history of synonymizations and indications of polyphyletic origin. Here we describe three new species of the genus, R. hypermnestra sp. nov., R. ruetzleri sp. nov. and R. agricola sp. nov., using conventional light microscopy, interference contrast microscopy and SEM. We provide 18S rRNA gene sequences of all three species, together with new sequences for the genera Catanema and Leptonemella. Both our morphological analyses as well as our phylogenetic reconstructions corroborate the genus Robbea. In our phylogenetic analysis the three species of the genus Robbea form a distinct clade in the Stilbonematinae radiation and are clearly separated from the clade of the genus Catanema, which has previously been synonymized with Robbea. Surprisingly, in R. hypermnestra sp. nov. all females are intersexes exhibiting male sexual characters. Our extended dataset of Stilbonematinae 18S rRNA genes for the first time allows the identification of the different genera, e.g. in a barcoding approach.